Coastal inundation deposit in the fluvial plain of Oued Mlaleh (Tangier Bay, Morocco) - Tichli Soufiane; Idrissi Mohamed Janati; Khalfaoui Otmane; Dezileau Laurent; Aboumaria Khadija (E3S Web of Conferences, 2024)
When it comes to natural disasters, tsunamis stand out for their destructive nature, leaving their mark on landscapes and human history. The tsunami of 1755 BCE is a major historical event that struck the countries around the Gulf of Cadix, inflicting significant damage to infrastructure and resulting in substantial human casualties. This study investigates a coastal inundation deposit located in the fluvial plain of Oued Mlaleh (Tangier Bay, northern Morocco). The Holocene sequence is studied using a multiproxy approach, involving sedimentological, morphoscopic, and micropaleontological analyses. These analyses collectively provide strong evidence of a high-energy event.